DOMESTIC VIOLENCE AGAINST WOMEN DURING THE PERIOD OF COVID-19 - Mamani Andres, Vilca; Erika Beatriz, Garcfa Castro; Calancho Mamani, Ernesto; Mamani Vitaliano, Enriquez; Apaza Mamani, Edson (The journal of contemporary issues in business and government, 2022)
Thearticleassessesdomestic violence against women during the non-COVID-2019 period and duringconfinement-2020, in Peru. The Logit model was used with 54,679 women. The probability of psychological violence in the study period was 45.6%, this probability increased by 2.1% during confinement; the probability of physical violence was 31.6%, with an increase of 2.2% during the pandemic, while the probability of sexual violence was 37.8% with a further increase of 5.6% during the COVID period. With enforced social isolation, domestic violence was higher because women spent more time at home with their spouses and was exacerbated by limited access to VAW services, domestic violence was higher among women in socially vulnerable situations and considered to be natives and with children under five years of age.